Do basketball scoring patterns reflect illegal point shaving or optimal in-game adjustments? - Jesse Gregory (Quantitative Economics, 2018)
This paper develops and estimates a model of college basketball teams' search for scoring opportunities, to provide a benchmark of the winning margin distributions that should arise if teams' only goal is to win. I estimate the model's structural parameters using first-half play-by-play data from college games and simulate the estimated model's predicted winning margin distributions. Teams' optimal state-dependent strategies generate patterns that match those previously cited as evidence of point shaving. The results suggest that corruption in NCAA basketball is less prevalent than previously suggested and that indirect forensic economics methodology can be sensitive to seemingly innocuous institutional features.
Keywords: C61; K42; L83; 330; Forensic economics; estimating dynamic games; point shaving